Hungarian Monitoring, 9 July 1988 . [Magyar rádiófigyelő], 1988. július 9 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Situation improving in Karabakh - Ceauşescu turns away West German delegation Domestic Affairs: - Preparations for Central Committee session - Interview with Ferenc Kárpáti on possibility of foreign troops' withdrawal - Interviews with Károly Grósz and Rezső Nyers - Young dawdlers - Lack of an information law Külpolitika - Javuló helyzet Karabahban - Ceauşescu elutasít egy nyugatnémet küldöttséget Belpolitika: - KB ülés előterjesztések - Interjú Kárpáti Ferenccel az idegen csapatok kivonásának lehetőségéről - Grósz Károly, Nyers Rezső interjú - Csellengő fiatalok - Az információs törvény hiánya